Reaching and Grasping in Autism Spectrum Disorder: A Review of Recent Literature - Sacrey, Lori-Ann R.; Germani, Tamara; Bryson, Susan E.; Zwaigenbaum, Lonnie (Frontiers in Neurology, 2014)
Impairments in motor functioning, which, until recently, have rarely been a primary focus in ASD research, may play a key role in the early expression of biological vulnerability and be associated with key social-communication deficits. This review summarizes current knowledge of motor behaviour in ASD, focusing specifically on reaching and grasping. Convergent data across the lifespan indicate that impairments to reaching and grasping emerge early in life, affect the planning and execution of motor programs, and may be impacted by additional impairments to sensory control of motor behaviour. The relationship between motor impairments and diagnostic outcomes will be discussed.